UPAYA MENINGKATKAN KREATIVITAS BELAJAR MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA PADA PESERTA DIDIK KELAS X SMA NEGERI 7 PONTIANAK - Putri, Kurnia Amelia; Asrori, Muhammad; Wicaksono, Luhur (Universitas Tanjungpura, 2025)
Learning creativity is also described as problem-solving ability because students are trained to think in achieving their goals. The general problem in this study is